User satisfaction analysis of graduates in the Pedagogic competence of alumni Indonesian language education development Indraprasta PGRI University - Adi permana; Bambang Sumadyo; Eko Yulianto (Journal of Instructional Development, Innovation, and Evaluation, 2022)
The purpose of this study was to analyze the satisfaction of graduate users with the pedagogic competence of the alumni of the Indonesian Language Education study program, Indraprasta University, PGRI. This research is a quantitative survey research with a correlation approach. Respondents in this study were stake holders (graduate users) who were alumni of Indonesian language education study programs in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek). Data obtained by giving questionnaires to graduate users about alumni job satisfaction and pedagogical competence. Based on the research results, it can be concluded that there is a significant effect of graduate user satisfaction on the pedagogic competence of graduates. This is evidenced by the value of Sig = 0.000 <0.05 and t count = 4.561. The magnitude of the correlation number is 0.484 with a determination of 0.234. This means that the magnitude of the relationship between X and Y variables is 0.484 in the medium category. The magnitude of the influence of X on Y is 23.4% where the variable user satisfaction of the graduates affects the pedagogical competence variable of graduates by 23.4% while the rest is influenced by other variables. Keywords: graduate user satisfaction, pedagogical competence, analysis